2014
DOI: 10.14693/jdi.v21i2.223
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Milk or its Combination with Tea and 0.2% NaF on Dental Enamel Demineralization Analyzed by Micro Computed Tomography

Abstract: Fluoride and calcium play an important role in the prevention of dental caries, promoting the inhibition of demineralization and the increase of remineralization. Objective: To investigate the effects of milk with/without the combination of tea and 0.2% NaF on enamel demineralization using micro-computed tomography (micro-CT). Methods: The coronal parts of 40 extracted sound premolars were prepared as tooth blocks. An unvarnished occlusal surface window was created for each tooth by covering the occlusal surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…Calcium and phosphor were the main mineral contained in soy milk and has an essential role in tooth and bone remineralization process. 12,13 In previous research conducted by Widyaningtyas 12 discovered a decreasing of enamel micropores depth in the teeth im-mersed with pure soy milk compared to artificial saliva as media for 8 hours in 14 days. High concentrated calcium and phos-phate, and low viscosity of soy milk accelerate precipitation of mineral calcium and phosphate thus lead to the enamel mi-croporosity closure happened and increased remineralization potential.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Calcium and phosphor were the main mineral contained in soy milk and has an essential role in tooth and bone remineralization process. 12,13 In previous research conducted by Widyaningtyas 12 discovered a decreasing of enamel micropores depth in the teeth im-mersed with pure soy milk compared to artificial saliva as media for 8 hours in 14 days. High concentrated calcium and phos-phate, and low viscosity of soy milk accelerate precipitation of mineral calcium and phosphate thus lead to the enamel mi-croporosity closure happened and increased remineralization potential.…”
Section: Introductionmentioning
confidence: 93%
“…Gunn and Woodward 3 reported a higher effectivity of pasteurized milk in enamel dissolution prevention than breast milk in vitro. Rahardjo et al 13 showed a higher protective effect against demineralization in the topical application of milk than a combined form of milk-tea and 0.2% milk-NaF. 13 Calcium, phosphate, and casein in milk inhibited demineralization and enhanced tooth remineralization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…membuktikan bahwa aplikasi topikal menggunakan susu memiliki efek perlindungan paling baik terhadap demineralisasi dibandingkan dengan aplikasi kombinasi susu-teh dan susu dengan 0,2% NaF. 6 Protein pada susu mempunyai komponen 80% kasein dan 20% whey. Kasein umumnya digunakan untuk pembuatan keju, sedangkan whey merupakan hasil sampingan dari pembuatan keju.…”
Section: Pendahuluanunclassified
“…Fluor dan kalsium yang terkandung di dalam susu memiliki peran yang penting dalam mencegah karies gigi, dengan membatasi demineralisasi dan meningkatkan remineralisasi. 6 Protein whey sebagai hasil sampingan dalam pembuatan keju, merupakan suatu jajaran pecahan protein yang ditemukan dalam susu. 5,12 Salah satu protein utama dalam protein whey adalah glikomakropeptida.…”
Section: Metode Penelitianunclassified